Late-Onset Bowel Strangulation due to Reduction En Masse of Inguinal Hernia. (1st April 2014) - Watanobe, Ikuo; Yoshida, Noritoshi; Watanabe, Shin; Maruyama, Toshirou; Ihara, Atsushi; Kojima, Kuniaki
Abstract : Incarcerated inguinal hernia is often encountered by surgeons in daily practice. Although rare, hernial reduction en masse is a potential complication of manual reduction of an incarcerated hernia. Manual reduction was performed in a case of Zollinger classification type VII (combined type) hernia in which the indirect hernia portion included an incarcerated small intestine. This procedure caused hernial reduction en masse, but this went unnoticed, and the remaining portion of the direct hernia in the inguinal region was treated surgically by the anterior approach. Because the incarcerated small bowel that had been reduced en masse was not completely obstructed, the patient's general condition was not greatly affected, and he was able to resume eating. Twenty days after surgery, he developed sudden abdominal pain as a result of gastrointestinal perforation. When performing manual reduction of an incarcerated hernia in cases after self-reduction over a long period, the clinician should always be aware of the possibility of reduction en masse.